The complete chloroplast genome sequence of Mentha canadensis (Labiatae), a traditional Chinese herbal medicine - Li Huaizhu; Yang Lin; Jiqing Bai; An Qiuyan; Dou Lingling; She Rui-Xue (Mitochondrial DNA. Part B. Resources, 2020)
Mentha canadensis is a well-known resource of traditional Chinese herbal medicine, belonging to the Mentha of the Labiatae family. In this study, the whole chloroplast genome of the M. canadensis chloroplast genome was sequenced, assembled and annotated, which contains 134 unique genes, including 89 protein-coding genes, 37 tRNA genes and 8 rRNA genes. A maximum likelihood phylogenetic tree based on 11 complete chloroplast genomes revealed that M. canadensis is closely related to M. longifolia and M. spicata. The chloroplast genome could be used for variety identification, genetic engineering and effective protection of germplasm resources.